7 - An investigation into factors impacting on exports from South Africa to the Southern African Development Community (SADC) - Collin Fish,; Chris Adendorff,; Kobus Jonker, (African Sociological Review, 2015)
Manufacturers face vigorous competition in local and export markets and need to have a genuine competitive advantage in order to grow. The South African government has recognised the importance of developing national manufacturing capacity as a means of increasing employment and reducing poverty. To this end, the government provides substantial support to both the manufacturing and exporting sectors. The government also negotiated the Southern African Development Community (SADC) agreement which leverages competitive advantages for South African manufacturers exporting into the region. However, since the ratification of the SADC agreement in 2008, there has been no perceptible increase in export activity to the region when compared to other markets. This research study was conducted to determine why this is the case and what factors are influencing the process. A structured literature review was undertaken to encapsulate export barriers, the role of the South African government in the export process, and the SADC agreement. The findings of the reviewed literature form the basis of the survey that led to the compilation of the research primary data. The results indicate that export barriers do not pose a major obstacle to trade into the SADC region. The role that the South African government holds was less conclusive with some successes noted, but on the whole the impact is not meaningfully positive. The SADC agreement and the dynamics prevailing in the free trade area do have a positive impact on exports to the region. The level of awareness with regard to the government support initiatives appears to be low.